Comparison of ancestral and traditional methods for elaborating sparkling wines - Arnau Just-Borràs; Ekaterina Moroz; Pol Giménez; Jordi Gombau; Elisa Ribé; Angels Collado; Pedro Cabanillas; Matteo Marangon; Francesca Fort; Joan M. Canals; Fernando Zamora (Current Research in Food Science, 2024)
This work compares the ancestral method for elaborating sparkling wines with the most widely used traditional method. Ancestral method is a single fermentation procedure in which the fermenting grape must is bottled before the end of alcoholic fermentation whereas traditional method involves a second fermentation of a base wine inside a bottle. Macabeo grapes were used to elaborate a traditional sparkling wine and two ancestral sparkling wines, one with a low yeast population and one with a high yeast population. The findings indicate that ancestral sparkling wines have lower ethanol content and can be elaborated using lower sulphur dioxide levels. In general, ancestral sparkling wines showed similar protein concentration, higher polysaccharide content, similar or better foamability (HM) than the traditional sparkling wine., No differences were found in the foam stability (HS). In addition, the sensory analysis indicated that ancestral sparkling wines have smaller bubble size, lower CO2 aggressivity, they seemed to have longer ageing time and were scored better than the traditional sparkling wine. These results therefore indicate that the ancestral method is of great interest for the elaboration of high-quality sparkling wines.